Integrating financial and digital literacy for quality primary education: A qualitative study on the Aku Bersedekah Comic and Prop Swap Folktales training - Eva Amalia; Maryam Isnaini Damayanti; Zulfin Rachma Mufidah; Heru S; Pratita P (Priviet Social Sciences Journal, 2025)
This is a qualitative analysis of the link between finance and digital literacy in primary school education. Two interrelated initiatives were conducted for the analysis. Aku Bersedekah comic book resources were utilized to facilitate the development of finance awareness and values among learners. The Prop Swap Folktales teacher training program permitted the upgrading of teaching staff digital literacy competence for narrative learning activities. Both efforts generated information using interviews, observations, and document analysis techniques for data acquisition. The results show that learners' basic finance knowledge and habits, such as saving, sharing, and management of money, became apparent because of the comic book program, while teacher training permitted upgrading of digital literacy for effective preparation of learning activities for schools. Therefore, finance and digital literacy initiatives have been shown to lead to the achievement of Sustainable Development Goal 4 because learning becomes innovative, values-driven, and technology-enabled.